2022
DOI: 10.1101/2022.07.10.22277380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sudden hearing loss following vaccination against COVID-19

Abstract: Importance Spontaneous adverse reaction reports of sudden hearing loss have been observed and a population-based cohort study conducted in Israel showed an increase in the incidence of sudden sensorineural hearing loss (SSNHL) following vaccination with messenger RNA COVID-19 vaccine BNT162b2 (Pfizer-BioNTech). However, in this setting, possibility of confounding remained. Objective To assess a potential association between COVID-19 vaccinations and SSNHL. Design A register-based country-wide observational s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…We did not examine the interval between vaccination and death in all included autopsies, as some authors have done (32)(33)35. All-cause mortality following COVID-19 vaccination has been studied on population level in Finland, and the hazard of death did not increase within 63 days of COVID-19 vaccination in Finland (63). Also, a meta-analysis including three self-controlled case series studies totaling 750,000 patients found no association between COVID-19 vaccination and all-cause mortality (64).…”
mentioning
confidence: 99%
“…We did not examine the interval between vaccination and death in all included autopsies, as some authors have done (32)(33)35. All-cause mortality following COVID-19 vaccination has been studied on population level in Finland, and the hazard of death did not increase within 63 days of COVID-19 vaccination in Finland (63). Also, a meta-analysis including three self-controlled case series studies totaling 750,000 patients found no association between COVID-19 vaccination and all-cause mortality (64).…”
mentioning
confidence: 99%